Designing Efficient College and Tax Policies - Sebastian Findeisen; Dominik Sachs (Institute for the Study of Labor (IZA), 2015)
The total social benefits of college education exceed the private benefits because the government receives a share of the monetary returns in the form of income taxes. We study the policy implications of this fiscal externality in an optimal dynamic tax framework. Using a variational approach we derive a formula for the revenue effect of an increase in college education subsidies and for the excess burden of income taxation caused by the college margin. We also show how the optimal nonlinear income tax problem is altered by the college margin. Our modeling assumptions are strongly guided by the recent structural labor literature on college education. The model incorporates multidimensional heterogeneity, idiosyncratic risk and borrowing constraints. The model matches key empirical results on college enrollment patterns, returns to education and enrollment elasticities. Quantitatively, we find that a marginal increase in college subsidies in the US is at least 70 percent self-financing through the net-present value increase in future tax revenue. When targeting this increase to children in the lowest parental income tercile, it is even up to 165 percent self-financing. The excess burden of income taxation is only slightly altered by the college margin and therefore the optimal Mirrleesian income tax schedule is barely affected as well, in particular if subsidies are set at their optimal level.
Keywords: H21; H23; I22; I24; I28; 330; optimal taxation; college subsidies; college enrollment; tax reforms